Design considerations for liquid crystal contact lenses. (6th November 2017) - Bailey, J; Kaur, S; Morgan, P B; Gleeson, H F; Clamp, J H; Jones, J C
Abstract: Switchable liquid crystal contact lenses with electrically controllable focal powers have previously been investigated as an alternative to bifocal contact lenses and spectacles for the correction of presbyopia. The simplest lens design uses a meniscus shaped cavity within the lens to contain the liquid crystal. The design of such a lens is considered in detail, including the nematic alignment and electrodes materials. The organic transparent conductor PEDOT:PSS was used as both electrode and planar alignment. Four different configurations are considered, using both planar and homeotropic orientations with either homogenous or axial alignment. Controllable switching of the focal power was demonstrated for each mode and focal power changes of up to Δ P = 3.3 ± 0.2 D achieved. Such lens designs offer significant potential for a novel form of correction for this common visual problem.